2022
DOI: 10.14336/ad.2021.1105
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing Clinical Trials in Aging-Related Tissue Fibrosis and New Findings Related to AhR Pathways

Abstract: Fibrosis is a pathological manifestation of wound healing that replaces dead/damaged tissue with collagen-rich scar tissue to maintain homeostasis, and complications from fibrosis contribute to nearly half of all deaths in the industrialized world. Ageing is closely associated with a progressive decline in organ function, and the prevalence of tissue fibrosis dramatically increases with age. Despite the heavy clinical and economic burden of organ fibrosis as the population ages, to date, there is a paucity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 232 publications
(235 reference statements)
0
3
0
Order By: Relevance
“…Tryptophan is an essential amino acid obtained through dietary sources and acts as a biosynthetic precursor to several microbial and host metabolites, including indole. 425,651 Notably, metagenomic analysis of PD gut microbiome has revealed a reduction in the tryptophan biosynthesis pathway. 331 Several indole derivatives, including indole-3-ethanol, indole-3-pyruvate, and indole-3aldehyde, maintain the integrity of the apical junctional complex and improve intestinal barrier integrity by activating the epithelial AHR (Fig.…”
Section: Points Of Intervention To Improve Microbiota-gut-brain Axismentioning
confidence: 99%
“…Tryptophan is an essential amino acid obtained through dietary sources and acts as a biosynthetic precursor to several microbial and host metabolites, including indole. 425,651 Notably, metagenomic analysis of PD gut microbiome has revealed a reduction in the tryptophan biosynthesis pathway. 331 Several indole derivatives, including indole-3-ethanol, indole-3-pyruvate, and indole-3aldehyde, maintain the integrity of the apical junctional complex and improve intestinal barrier integrity by activating the epithelial AHR (Fig.…”
Section: Points Of Intervention To Improve Microbiota-gut-brain Axismentioning
confidence: 99%
“…[ 4 ] Aryl hydrocarbon receptor (AhR) is a cytoplasmic receptor and mainly expressed at barrier surfaces, including the skin, respiratory tract, and gastrointestinal tract, linking environmental, microbial, and metabolic cues to biological and pathophysiological changes through regulating complex transcriptional programs. [ 5 6 7 8 ] In recent years, mounting evidence has revealed that AhR plays an important role in regulating environmental factor-triggered age-associated phenotypes. The human lung is one of the important organs highly impacted by aging and has the largest surface area exposed to environmental pollutants and biological, immunological, and xenobiotic stress.…”
Section: Introductionmentioning
confidence: 99%
“…The burden of fibrosis is significant, and twenty-five percent of the world's population is affected [ 3 ]; the annualized incidence of major fibrosis-related conditions is approaching five percent [ 2 ]. Aging is closely related to the progressive decline in organ function [ 4 ]. The accumulation of senescent cells is a major feature of organismal aging [ 5 ].…”
Section: Introductionmentioning
confidence: 99%